Pendampingan Program BTQ (Baca Tulis Al-Qur’an) untuk Meningkatkan Kualitas Membaca dan Menulis Al-Qur’an pada Peserta Didik SD Negeri 2 Sidoharjo Kecamatan Pulung - Siti Faizatur Rosyidah; Medina Nur Asyifa Purnama (Social Science Academic, 2023)
This Community Service Lecture in BTQ Program Assistance is a good step to develop. The purpose of this study is to find out how the assistance of the BTQ (Read and Write the Qur'an) program at SD Negeri 2 Sidoharjo in addition to finding out whether the BTQ (Read and Write Al-Qur'an) program can improve the ability of Qur'an Learning students at SD Negeri 2 Sidoharjo. The service method used is in the form of Asset Based Community Development (ABCD). In carrying out the assistance of the BTQ program, it is carried out by reading, listening and individual writing practice. With the assistance of this BTQ program, the impact and benefits that can be seen and felt include, students are more familiar with and can read and write verses of the Qur'an, reducing Arabic illiteracy.